Nexilin Is a New Component of Junctional Membrane Complexes Required for Cardiac T-Tubule Formation. Issue 1 (2nd July 2019) - Liu, Canzhao; Spinozzi, Simone; Chen, Jia-Yu; Fang, Xi; Feng, Wei; Perkins, Guy; Cattaneo, Paola; Guimarães-Camboa, Nuno; Dalton, Nancy D.; Peterson, Kirk L.; Wu, Tongbin; Ouyang, Kunfu; et al.
Abstract : Background: Membrane contact sites are fundamental for transmission and translation of signals in multicellular organisms. The junctional membrane complexes in the cardiac dyads, where transverse (T) tubules are juxtaposed to the sarcoplasmic reticulum, are a prime example. T-tubule uncoupling and remodeling are well-known features of cardiac disease and heart failure. Even subtle alterations in the association between T-tubules and the junctional sarcoplasmic reticulum can cause serious cardiac disorders. NEXN (nexilin) has been identified as an actin-binding protein, and multiple mutations in the NEXN gene are associated with cardiac diseases, but the precise role of NEXN in heart function and disease is still unknown. Methods: Nexn global and cardiomyocyte-specific knockout mice were generated. Comprehensive phenotypic and RNA sequencing and mass spectrometry analyses were performed. Heart tissue samples and isolated single cardiomyocytes were analyzed by electron and confocal microscopy. Results: Global and cardiomyocyte-specific loss of Nexn in mice resulted in a rapidly progressive dilated cardiomyopathy. In vivo and in vitro analyses revealed that NEXN interacted with junctional sarcoplasmic reticulum proteins, was essential for optimal calcium transients, and was required for initiation of T-tubule invagination and formation. Conclusions: These results demonstrated that NEXN is a pivotal component of the junctional membrane complex and is required for initiation and formation of T-tubules, thus providing insight into mechanisms underlying cardiomyopathy in patients with mutations in NEXN . Abstract : Supplemental Digital Content is available in the text.